Fine-scale Antarctic grounded ice cliff 3D calving monitoring based on multi-temporal UAV photogrammetry without ground controlMendeley DataSource code - Shuhang Zhang; Lei Zheng; Huizhou Zhou; Qiuyang Zhao; Jie Li; Yinyue Xia; Wuming Zhang; Xiao Cheng (International Journal of Applied Earth Observations and Geoinformation)
Grounded ice cliffs in Antarctica contribute directly to global sea level rise through calving, yet they are less studied compared to floating ice shelves. Traditional satellite remote sensing methods face limitations in temporal and spatial resolution for monitoring these small-scale calving events. This research aims to develop a method for fine-scale monitoring of grounded ice cliff calving using multi-temporal UAV photogrammetry without ground control points, with assistance from in-situ snow pit measurements. The methodology involves co-aligning UAV images to create consistent 3D models, followed by detecting calving events based on significant local volume changes between successive models. Noise filtering strategies were implemented to exclude outliers, and calving volume and mass were calculated using measurements of snow depth and density. Our method was conducted near the China’s Qinling Station on Inexpressible Island in Victoria Land, East Antarctica, and achieved a co-alignment accuracy of 2.69 cm. Over a 26-day observation period with 10 repeated flights, 44 calving events were identified along the coastline of 0.89 km, resulting in a total calving volume of 4506.69 m3 and a mass of 3078.45 tons. The average calving rate was determined to be 262.93 tons per kilometre per day along the coastline. This study demonstrates the effectiveness of fine-scale monitoring of grounding ice-cliff calving using UAV photogrammetry in polar environments. Further research is necessary to identify the spatial distribution of the Antarctic grounded ice cliffs and to quantify the total mass loss.